METHODS TO INCREASE OIL WELL EFFICIENCY - Mansurov Aziz Abdikarimovich (European Science Publishing, 2024)
This article explores various methods aimed at increasing the efficiency of oil wells, focusing on advanced drilling techniques, enhanced oil recovery (EOR) methods, and real-time data analytics. The article discusses how these technologies can help operators extract more oil from existing wells, reduce costs, and extend the lifespan of the oil field.
Keywords: Oil well efficiency, enhanced oil recovery, drilling techniques, data analytics